PEMANFAATAN DIGITAL BRANDING DALAM UPAYA PENINGKATAN PEMASARAN DI CV. KAYOO - Hikmah, Fatimah Fahimatul; Kriya, Istian (Jurnal Terapan Ekonomi dan Bisnis, 2026)
This report was prepared based on internship activities carried out at CV. Kayoo, a company that focuses on the production and sale of home decorations using acrylic and wood materials. with the aim of understanding and carrying out the process of creating digital content as a product marketing strategy. The research was conducted using descriptive qualitative methods with an observation and documentation approach during the internship period. The study results indicate that the way digital content is created on CV. Kayoo involves four main steps, namely: collecting product data, compiling a timeline, producing videos and photos, and editing content. Each phase has a crucial function to ensure that the content created meets marketing needs and is able to attract consumer interest.   Keywords : Digital Branding; Digital Content; Marketing Strategy; MSMEs; CV. Kayoo